PENINGKATAN KEAKTIFAN DAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN KOOPERATIF TEAMS GAMES TOURNAMENT (TGT) PADA MATERI STRUKTUR ATOM DI KELAS X SMA - Azkia Rahmi; Al Mumtahanah Savira; Erma Yanti; Nadya Ribka Yolanda Rajagukguk; Selvia Anggrayne; Putri Andini; Marnida Yusfiani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research was motivated by the low level of student activeness and learning outcomes in chemistry, specifically on Atomic Structure material at SMAN 13 Medan. The learning process applied was predominantly conventional and teacher-centered (teacher centred), causing students to become passive and unmotivated. This study aims to improve student activeness and learning outcomes through the cooperative learning model Teams Games Tournament (TGT) on Atomic Structure material. The method used was Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, action, observation, and reflection stages. Subjects were 36 students of class X-1 SMAN 13 Medan in the 2025/2026 academic year. Data were collected through multiple-choice test instruments to measure cognitive learning outcomes and non-test instruments (observation sheets) to measure student activeness and teacher performance. Descriptive comparative analysis was used to compare improvements from pre-cycle to the second cycle. Results showed that the average N-Gain increased from 0.47 (moderate) in Cycle I to 0.76 (high) in Cycle II. The percentage of students achieving the minimum passing grade (KKM) rose from 47% in Cycle I to 76% in Cycle II. It is concluded that the TGT cooperative learning model is effective in improving student activeness and learning outcomes on Atomic Structure material